(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2007)
The article deals with the issue of estimation of the area models errors determined on the basis of a discrete points set with the given values of space coordinates (x, y, z). The object was assumed to be described by shape functions in the form of the elliptic paraboloid and the hyperbolic paraboloid. The digital task accomplishment consisted in the statistic verification of errors of the models determined by neural networks and by the accomplishment of adjustment tasks. Modeling by the means of neural networks was carried out by the unidirectional multilayer networks with the application of gradient methods of optimalization and by Resilientback Propagation algorithm (RPROP). The obtained results were compared with the following results of approximation of the second and the third degree of polynomial, the b-spline function and the kriging’s method.